Analysing revisions in online writing - Haugaard, Rikke Hartmann; Dam Jensen, Helle (HERMES - Journal of Language and Communication in Business, 2019)
New technology has given new insights into the writing process of professional text producers. Keystroke logging can give the researcher knowledge about how text producers write and revise their texts, both at the level of form and content. With a point of departure in the results of Haugaard’s (2016) study of journalistic writing, this article suggests a reassessment of the online revision taxonomy developed by Lindgren/Sullivan (2006b), with a focus on external revisions. In order to be able to interpret the effect of online revisions on the text by means of keystroke logging, it is proposed that revisions be analysed with a point of departure in the semantic content involved, rather than according to location, i.e. in the text already transcribed (contextual revision) or in the text currently being transcribed (pre-contextual revision), as suggested by Lindgren/Sullivan (2006b). It is argued that contextual and pre-contextual revisions should not be conceptualised as dichotomous entities, but as open categories on a continuum of semantically meaningful context, on the basis of which revisions can be interpreted depending on the degree of completeness of the context in which they are made.